Revisiting the Operating Room Basics - Tushar Chakravorty (Bengal Journal of Otolaryngology and Head Neck Surgery, 2015)
Young doctors walking into the operating room are eager to develop their skills to become efficient and knowledgeable professionals in future. But precious little is done to actively develop the basic practical skills of the budding doctors. They remain unaware about the layout of the operating room, the OR etiquette and often do not have sound scientific understanding and importance of meticulous execution of the basic operating room protocols.